DISCRIMINATION BETWEEN WEIBULL AND LOGNORMAL DISTRIBUTIONS FOR LIFETIME DATA - Pasha, G. R.; Khan, M. Shuaib; Pasha, Ahmed Hesham (Journal of Research (Science), 2006)
Reliability and failure data, both from life testing and from in-service records, are often modeled by the Weibull or Lognormal distributions so as to be able to interpolate and/or extrapolate results. The aim of this research is to discriminate between the Weibull and Lognormal distributions for complete samples. Both reliability models Weibull and Lognormal are then illustrated. Median rank regression (MRR) and maximum likelihood estimation (MLE) data- fitting methods are described and goodness-of-fit using maximum likelihood ratio (MLR) and most powerful invariant (MPI) tests. We find the Weibull distribution better for fitting to lifetime data when comparing with the Lognormal distribution.